Arbeidsstedet som læringsarena for videreutdanning i praksisveiledning: –En fokusgruppestudie med ledere og sykepleiere - Blekken, Lene Elisabeth; Antonsen, Therese; Wangen, Margret Gyda; Murray, Cecilie Lund; Greaker, Tove Kristin (Nordisk Tidsskrift for Helseforskning, 2025)
Background: Future healthcare services depend on competent nurses. Nurse preceptor competence is crucial for the students’ development and learning during clinical studies. However, it seems challenging for the health services to find resources to prioritize competence development in mentoring, and to motivate nurses to further educate themselves in mentoring. Purpose: To gain knowledge of a new educational model for mentoring education with the workplace as the learning arena. Method: Qualitative design with focus groups. Result: An educational model with the workplace as the learning arena, may promote learning and contribute to nurses changing their mentoring practice from an experience-based to an evidence-based mentoring practice. To succeed, it is important with good teamwork between the educational institution and the clinical setting. Conclusion: An educational model with the workplace as a learning arena and integrated into the SVIP model, can contribute to increased interest and motivation for competence development in mentoring.